GENDER INEQUALITY POLITICS - Meltem ÜNAL ERZEN (Fırat University, 2019)
In this article, gender inequality against women has been discussed from a political perspective. Insufficient representation of women in the political arena has been brought about by the fact that women are secondary almost in all parts of social life. Not being able to realize equal representation and participation, which is a requirement of true democracy, causes not only an inequality between men and women but also a fundamental problem of democracy. The non-representation of half the population in the decision-making process demonstrates that the decisions made are neither pluralistic nor democratic. Thus, women need to be represented equally or at least above critical thresholds in the political stage, in order to strengthen the democratic life and to put an end to gender inequality. Regardless of some improvements in the conditions of work, representation of women in politics, who make up half the population, is not enough for various reasons. Even though several studies have concluded that the problem of underrepresentation is due to many factors, the true cause can be said to be the patriarchal structure in the male-dominated societies. The most recent Global Gender Inequality Report, published annually by World Economic Forum (WEF), clearly demonstrates the graveness of inequality with a table showing the women's rights in areas like politics, economy and education. According to the report, even though 88 countries from 149 in which the study was conducted has shown progress in salaries and equality at political representation, the overall situation is still haunting in gender inequality. The report adds that it would take more than a century to solve gender inequality on a global scale, and a hundred years seems optimistic in some areas. A requirement to meet a 30% threshold in general and local elections for both genders has been implemented by the new Political Parties Act (2015) in Turkey. This so-called gender quota system has been effectuated either voluntarily or through the internal constitution of the political parties and organizations therefore becoming a recent legal requirement. However, when the application of this requirement is closely examined, it can be seen that the critical thresholds are not met and therefore representation of women are still too low.